Global Transcriptome Analysis During Adipogenic Differentiation and Involvement of Transthyretin Gene in Adipogenesis in Cattle - Cai, Hanfang; Li, Mingxun; Sun, Xiaomei; Plath, Martin; Li, Congjun; Lan, Xianyong; Lei, Chuzhao; Huang, Yongzhen; Bai, Yueyu; Qi, Xinglei; Lin, Fengpeng; Chen, Hong (Frontiers in Genetics, 2018)
Adipose tissue plays central role in determining the gustatory quality of beef, but traditional Chinese beef cattle have low levels of fat content. We applied RNA-seq to study the molecular mechanisms underlying adipocyte differentiation in Qinchuan cattle. A total of 18,283 genes were found to be expressed in preadipocytes and mature adipocytes, respectively. 470 of which were significantly differentially expressed genes (DEGs) (false discovery rate (FDR) values < 0.05 and fold change ≥ 2). In addition, 4534 alternative splicing (AS) events and 5153 AS events were detected in preadipocytes and adipocytes, respectively. We constructed a protein interaction network, which suggested that collagen plays an important role during bovine adipogenic differentiation. We characterized the function of the most down-regulated DEG (P < 0.001) among genes we have detected by qPCR, namely, the transthyretin (TTR) gene. Overexpression of TTR appears to promote the expression of the peroxisome proliferator activated receptor γ (PPARγ) (P < 0.05) and fatty acid binding Protein 4 (FABP4) (P < 0.05). Hence, TTR appears to be involved in the regulation of bovine adipogenic differentiation. Our study represents the comprehensive approach to explore bovine adipocyte differentiation using transcriptomic data and reports an involvement of TTR during bovine adipogenic differentiation. Our results provide novel insights into the molecular mechanisms underlying bovine adipogenic differentiation.